THE USE OF INTELLIGENT TRANSPORTATION SYSTEMS IN BALAD DISTRICT USING GEOGRAPHIC INFORMATION SYSTEMS (GIS) - Saleh, Muzafar Abdul Nabi (Journal of Geography, Regional Planning and Development, 2025)
Objective: This research aims to employ Intelligent Transportation Systems (ITS) in the Balad District through the use of Geographic Information Systems (GIS). Method: The study area lies between latitudes (37°44′48″ and 37°71′61″) north and longitudes (48°11′24″ and 49°49′25″) east, covering a total area of (2161.34 km²), equivalent to (592,145 donums). Through the analysis of the road network, the study identifies the fastest routes between specific points (e.g., from point A to point B). Service area analyses (cumulative and multiple) illustrate how accessibility changes with increased barriers; for example, determining the number of hospitals accessible within 5, 10, and 15 minutes’ drive from schools. Additionally, by analyzing traffic data, the accessibility of hospitals may vary according to traffic conditions. Results: Key requirements for the successful implementation of ITS include political commitment, sufficient budget allocations to ensure project sustainability, the establishment of traffic control centers for monitoring and managing traffic remotely, and the creation of a central database containing information on vehicles and road networks. Novelty: The study integrates ITS and GIS in the Balad District to identify optimal routes and assess service accessibility dynamically based on traffic conditions, highlighting infrastructural and administrative requirements for effective ITS deployment.